Job search of dual-career families in Finland - Taru Järvinen (European Regional Science Association (ERSA), 2003)
This contribution focuses on the job search behaviour of Finnish professionals and its differences by the types of labour market areas. In the turn of 21st century the educational level have risen and the number of professionals have increased. At the same time the migration intensity have grown and concentrated towards versatile labour market areas, so called growth centres. The dual-career families are strongly concentrated to main local labour market areas but there are also exceptions. The main purpose of the study is to figure out the structural and regional differences of job search for different parts of the country car according to the search theory the residential relocation decision is depending on the job search strategies. The attention will be paid both to those hypothetical job search regions defined by the families them selves and to the recent work locations and commuting experiences related to the family history, career histories and residential mobility history of past years. The data is longitudinal sample data dealing Finnish families where both spouses are educated professionals.
Keywords: 330